HUBUNGAN ANTARA KESELAMATAN KERJA DENGAN PRODUKTIVITAS KERJA KARYAWAN - Feryana Dwi Rahayu (Ilmu Psikologi Universitas Yudharta Pasuruan)
Increasing the empowerment of workers engaged in industry and services, to improve work productivity is very important to be pursued, because with the good work productivity, so the company will be able to develop and achieve goals. The effort that can be tried by the company is, provide attention and protection of work safety, so there will be a good relations between employees and the company. The purpose of this research is, to find out the relations between work safety and employees productivity in production. The results showed that there was a relations between work safety and employees productivity. And accepted at the 1% significance level, where the rxy of 64,926 is greater than r table of 0.561. so, more higher work safety, then employee work productivity will more increase. And, more lower the work safety, then work productivity will more decrease.